The Return of the Native - Hardy, Thomas, 1840-1928 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Return of the Native" by Thomas Hardy is a novel published in 1878. Set entirely on the wild Egdon Heath, it follows the intersecting fates of several characters over one fateful year. When Clym Yeobright returns from Paris, the beautiful but restless Eustacia Vye sees him as her escape from the desolate heath. Their romance ignites conflicts with family and former lovers, including the fickle Damon Wildeve and sweet Thomasin. Misunderstandings, thwarted ambitions, and passionate desires converge in this atmospheric tale of longing and consequence. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Return_of_the_Native
Release date is 2006-01-12
E-text prepared by Joseph E. Loewenstein, M.D., and John Hamm
Keywords: Adultery -- Fiction; Didactic fiction; Love stories; Mate selection -- Fiction; Wessex (England) -- Fiction; Mothers and sons -- Fiction; People with visual disabilities -- Fiction; Heathlands -- Fiction